A Review on Microorganisms Important to Bioremediation (International Journal of Innovative Research in Engineering & Management, 2023)
Industrialization, population explosion, or  changing lifestyles have led in the creation of non degradable contaminants harming the environment and  human health. Biological methods employing  microorganisms are gaining significance as an eco-friendly  and cost-effective alternative to reduce the pollution  burden. Microorganisms can live in a diverse environment  and generate metabolites that may breakdown and convert  toxins making it possible to resuscitate polluted areas  naturally. Natural microbiomes have also been exploited in  a variety of bioremediation approaches. New tools for  studying bacterial activity in polluted or bioremediated  sites have been developed as a result of recent  breakthroughs in molecular bacterial communities. Such  investigations provide information that aids in the  evaluation of bioremediation effectiveness or the creation  of techniques to speed up bioremediation.
Keywords: Bacterial; Bioremediation; Environment; Microorganisms